Regulatory approaches to consumer protection in the financial sector and beyond: Toward a smart disclosure regime? - REMOLINA, Nydia (Institutional Knowledge at Singapore Management University, 2020)
Traditionally, consumer and data protection policies evolved from issues of consent and information disclosure. The purpose of these regulatory approaches is the protection of consumers by reducing some contracting failures, such as asymmetries of information and a lower bargaining power, especially in transactions involving complex issues such as financial products and sensitive personal data. In the past, regulators have responded to privacy and consumer protection by adopting what this paper refers to as an “imperfectly informed regime”, in which consumers do not receive full information about the risks associated with their decisions, even if they are still protected through a variety of ex post mechanisms such as the judicial system or a consumer protection authority. Recently, jurisdictions, such as the European Union, have adopted a “perfectly informed regime” for data protection based on the idea of full disclosure. While this approach has advantages, it does not effectively assure consumers understand the consequences and risks associated with their decisions. Unless the system still provides reliable mechanisms ex post to protect consumers, there will still be a high risk of opportunism of merchants vis-à-vis consumers. As a response to the weaknesses existing in the traditional regulatory approaches to protect consumers, behavioural economists have proposed a new system based on the idea of ‘smart disclosure’. According to this system, consumers should get an understanding of their decisions by requiring counterparties to provide a clear information about the content and associated risks. Despite the popularity of this regulatory approach, this paper argues that it is not perfect either. Namely, it will be pointed out that, even though the smart disclosure system can be desirable for countries without reliable institutions to protect consumers ex post, the adoption of this regulatory approach faces several challenges. Therefore, countries with efficient mechanisms ex post to protect consumers may find the traditional regulatory models more desirable. The paper concludes by arguing that despite the favour towards systems of smart disclosure or perfectly informed regimes, the most desirable one will depend on the particular features of a country.